Sistem Pendukung Keputusan Pemilihan SMA/SMK Terbaik di Kabupaten Malaka dengan Metode COPRAS - Abubakar, Muhammad Alfazrin; Bulan, Semlinda Juszandri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
In the current era of globalization, the process of choosing a high school/vocational school has become a complex decision for prospective students who are trying to determine where to pursue their studies. This research explores the implementation of the Complex Proportional Assessment (COPRAS) method to aid in decision-making regarding the selection of Senior High School/Vocational School in Malacca Regency. With 35 high schools and 7 vocational schools in competition, Malacca Regency strives to produce the best graduates. This study specifically focuses on Senior High School/Vocational School in Central Malaka District as a viable alternative. The objective is to assist and simplify the decision-making process for students and parents when selecting the high school/ vocational school for prospective students. Data collection involved observation, interviews, and literature review, with criteria such as accreditation, number of students, SPP and the number of teachers considered, and Senior High School/Vocational School in Central Malaka District as the alternative. The data obtained will be implemented in a Decision Support System (DSS) based on the Complex Proportional Assessment (COPRAS) method to produce the relative value of each alternative and utility value for ranking. The results of this research are that the system provides information on selecting the best high school/vocational school based on COPRAS analysis and helps prospective students make more rational and data-based decisions.